High-Resolution Imaging Reveals New Features of Nuclear Export of mRNA through the Nuclear Pore Complexes - Kelich, Joseph M. (MDPI, 2014)
The nuclear envelope (NE) of eukaryotic cells provides a physical barrier for messenger RNA (mRNA) and the associated proteins (mRNPs) traveling from sites of transcription in the nucleus to locations of translation processing in the cytoplasm. Nuclear pore complexes (NPCs) embedded in the NE serve as a dominant gateway for nuclear export of mRNA. However, the fundamental characterization of export dynamics of mRNPs through the NPC has been hindered by several technical limits. First, the size of NPC that is barely below the diffraction limit of conventional light microscopy requires a super-resolution microscopy imaging approach. Next, the fast transit of mRNPs through the NPC further demands a high temporal resolution by the imaging approach. Finally, the inherent three-dimensional (3D) movements of mRNPs through the NPC demand the method to provide a 3D mapping of both transport kinetics and transport pathways of mRNPs. This review will highlight the recently developed super-resolution imaging techniques advanced from 1D to 3D for nuclear export of mRNPs and summarize the new features in the dynamic nuclear export process of mRNPs revealed from these technical advances.